[PP.22.18] UROTENSIN II EXERTS PRESSOR EFFECTS BY STIMULATING RENIN AND ALDOSTERONE SYNTHASE GENE EXPRESSION. (September 2017) - Caroccia, B.; Menegolo, M.; Seccia, T.M.; Petrelli, L.; Limena, A.; Porzionato, A.; Poglitschc, M.; Rossi, G.P.
Abstract : Objective: The pressor effects of the potent vasoconstrictor Urotensin II (UII) remain uncertain. We investigated the effects of UII on blood pressure (BP) and the renin-angiotensin-aldosterone system. Design and method: We randomized normotensive Sprague-Dawley rats into 4 groups that received a 7-days UII infusion (cases, 600 pmol/kg/h) or a vehicle (controls). Group 1 received a normal sodium intake; Group 2 underwent unilateral nephrectomy and salt loading; Group 3 received spironolactone, besides unilateral nephrectomy and salt loading; Group 4 only received spironolactone. BP was monitored by radio-telemetry; changes of gene and protein level of renin and Cyp11b2 expression were measured. Results: UII raised BP transiently after a lag phase of 24–48 hours in Group 1, and progressively over the week in Group 2. Spironolactone abolished both pressor effects of UII. UII increased by 7-fold the renal expression of renin in Group 2 rats (p < .01 vs control); it also increased aldosterone synthase expression (p < .01, both gene and protein level) in the adrenocortical zona glomerulosa, and prevented the blunting of renin expression induced by high salt. Double immunohistochemistry showed localization of renin and UII receptor in the human renal cortex. Conclusions: UII raises BP transiently when sodium intake and renal function are normal, but progressive in salt-loaded uni-nephrectomized rats. Moreover, UII counteracts the suppression of renin induced by salt loading and stimulation of aldosterone secretion. This novel action of UII in the regulation of renin and aldosterone synthesis can play a role in several clinical conditions where UII levels are up-regulated.